AB1182 Efficacy and safety of canakinumab, fully human anti-interleukin-1beta antibody, in systemic juvenile idiopathic arthritis. (23rd January 2014) - Ruperto, N.; Brunner, H.; Quartier, P.; Constantin, T.; Wulffraat, N.; Horneff, G.; Brik, R.; McCann, L.; Kasapcopur, O.; Rutkowska-Sak, L.; Schneider, R.; Berkun, Y.; et al.
Abstract : Background: Systemic juvenile idiopathic arthritis (SJIA) is an IL1β-mediated autoinflammatory disease, characterized by spiking intermittent fever, rash, and arthritis. Canakinumab (CAN), a selective, fully human, anti-IL1β monoclonal antibody has shown promising efficacy and safety data in SJIA patients (pts). Objectives: To demonstrate CAN allows tapering of corticosteroids (CS) and to evaluate time to flare in CAN vs placebo (PCB) pts with SJIA and active systemic features. Methods: This Phase 3 trial had two parts. In Part 1 (P1), all patients (2-20 yrs) received open label CAN to identify responders and to taper CS. In Part 2 (P2), pts who successfully tapered their CS were randomized to receive CAN or PCB. In P1, pts received CAN (4mg/kg; max 300 mg) sc injection every 4 wks. Primary objectives were to determine if ≥25% of pts on CS at study entry could successfully taper the CS dose (P1); if time to flare was longer for CAN vs PCB (P2), and safety. Results: 177 pts (128 on CS; 49 steroid-free) entered P1, of which 100 pts (CAN, n=50; PCB, n=50) entered P2; most of the remaining 77 pts were eligible (>ACR30 at Day 15) to directly enter an open-label extension study following P1. In P1, 92 pts attempted CS tapering and 57 (62%) were successful, representing 44.5% (57/128; p<0.0001) of pts on CS at study entry. 46% (42/92) of pts who attempted CS reduction and 33% (42/128) of pts on CS at study entry discontinued the CS. In P2, the median time to flare was 236 days (95%CI: 141-449 days) for PCB vs not determinable for CAN as <50% had flared, corresponding to a 63% relative risk reduction in flare for CAN vs PCB (HR 0.37; 95%CI: 0.17-0.78; p=0.0043). In P1, 78% (138/177) of pts had AEs, of which infections of the upper respiratory tract were the most common. Five pts discontinued due to an AE and 14 pts had ≥1 SAE; mostly infections, MAS, or flare-associated events. 1 pt on CAN had died with MAS. In P2, a direct comparison of safety between the 2 groups was difficult as all pts were exposed to CAN in P1. 80% of pts on CAN and 70% on PCB had ≥1 AE, with infections of the upper respiratory tract being the most common in both groups. 4 pts on PCB discontinued due to an AE, and SAEs were reported in 6 pts in each group; mostly due to an infection, MAS, or flare-associated event. 1 fatal MAS case occurred in 1 pt after 6 months of PCB. Conclusions: For SJIA patients with active features, canakinumab sc injection every 4 weeks allowed successful steroid tapering, with one third being able to discontinue their CS. Canakinumab significantly decreased the risk of SJIA flare, while demonstrating an acceptable safety and tolerability profile. Disclosure of Interest: N. Ruperto Grant/Research support from: Abbott, Astrazeneca, Bristol Myers and Squibb, Centocor Research & Development, Eli Lilly and Company, "Francesco Angelini" s.p.a, Glaxo Smith & Kline, Italfarmaco, Merck Serono, Novartis, Pfizer Inc., Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers Bureau: Astrazeneca, Novartis, Bristol Myers and Squibb, Roche, Janssen Bilogics B.V., H. Brunner Consultant for: Novartis, UCB, Genentech, Jansen, GSK and Medimmune, Paid Instructor for: Participant in Scientific Advisory Committee for Canakinumab program in SJIA, P. Quartier Speakers Bureau: Novartis, T. Constantin: None Declared, N. Wulffraat: None Declared, G. Horneff Grant/Research support from: Abbott, Pfizer, Consultant for: Abbott, Pfizer, Novartis, Roche, R. Brik: None Declared, L. McCann: None Declared, O. Kasapcopur: None Declared, L. Rutkowska-Sak: None Declared, R. Schneider Consultant for: Hoffman-La-Roche, Speakers Bureau: Hoffman-La-Roche, Y. Berkun: None Declared, I. Calvo: None Declared, M. Erguven Grant/Research support from: Novartis, L. Goffin: None Declared, M. Hofer Consultant for: Novartis, T. Kallinich Speakers Bureau: Novartis, S. Knupp: None Declared, Y. Uziel Consultant for: Novartis, S. Viola: None Declared, K. Nistala Grant/Research support from: Arthritis Research UK Career Progression Fellow, C. Wouters: None Declared, R. Cimaz: None Declared, M. Ferrandiz Grant/Research support from: Novartis, B. Flato: None Declared, M. Luz Gamir: None Declared, I. Kone-Paut: None Declared, A. Grom Consultant for: Novartis, J&J, B. Magnusson Grant/Research support from: Swedish Association of local Authorities and Regions, Consultant for: Roche AB, S. Ozen Consultant for: Novartis, F. Sztajnbok: None Declared, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, D. Kim Shareholder of: Novartis, Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, A. Martini Grant/Research support from: Abbott, Astrazeneca, Bristol Myers and Squibb, Centocor Research & Development, Eli Lilly and Company, "Francesco Angelini" s.p.a, Glaxo Smith & Kline, Italfarmaco, Merck Serono, Novartis, Pfizer Inc., Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers Bureau: Astrazeneca, Novartis, Bristol Myers and Squibb, Glaxo Smith & Kline, D. Lovell Consultant for: Abbott Laboratories, Centocor Inc, Amgen, Astra Zeneca Pharmaceutical, Bristol-Myers Squibb, Hoffmann-La Roche, Inc., Novartis Pharmaceutical Corporation, Pfizer Inc, Regeneron, UBC, Wyeth Pharmaceuticals, Xoma Corporation, Speakers Bureau: Wyeth Pharmaceuticals